Moringa olifera Leaf Meal as an Alternative Protein Feed Ingredient in Broiler Ration - Tesfaye , Etalem; Animut, Getachew; Urge, Mengistu; Dessie, Tadelle (International Journal of Poultry Science, 2013)
A total of 300 Hubbard Classic day-old broiler chicks were randomly distributed into 15 pens equally, representing 5 feeding treatments to evaluate the performance of chicks fed varying dietary levels of Moringa Olifera Leaf Meal (MOLM) replacing soybean meal (SBM) up to the age of 56 days. Treatments were inclusion of MOLM at 0 (T1), 5 (T2), 10 (T3), 15 (T4) and 20% (T5). Four birds 2 from each sex were randomly selected from each replication for carcass evaluation at the end of the study. From the same birds used for carcass evaluation, blood was taken for serum Total Cholesterol (TC) and Total Protein (TP) determination. The crude protein content of MOLM was 28%. Daily Dry Matter (DM) intake during the entire experimental period ranged 54 to 75 g/bird and was greater (P<0.05) for T1 than T3 and T5. Daily body weight gain for the entire experimental period were 29, 25, 22, 22 and 17g (SEM = 1.0) for T1, T2, T3, T4 and T5, respectively and values were greater for T1 as compared to T3, T4 and T5 but similar (P>0.05) with T2. Replacement of MOLM for SBM lowered (P<0.05) yield of most parameters such as dressed weight, eviscerated weight, breast weight, thigh weight, drumstick weight and giblet weight. Sex differences were significant in drumstick weight and drumstick and thigh percentages with greater values for males than females. Conversely, eviscerated percentage was greater (P<0.05) for females than males. Levels of TC and TP were greater for T3 than T1, T4 and T5 (P<0.05). However, differences in TC and TP levels due to sex were not significant (P>0.05). Depending on the production parameters measured, MOLM can be substituted to SBM in broilers diet up to a level of 5% inclusion in the total ration without negative effect on biological performance. Levels of MOLM substitution to SBM of 10-20% appeared to reduce growth rate but did not have an adverse effect on the health of birds, indicating the potential of the plant as an alternative feed ingredient in poultry feeding.